CFD simulation of a cold flow model of inter-connected three fluidized reactors applied to chemical looping hydrogen production. (April 2022) - Yurata, Tarabordin; Tang, Liangguang; Feng, Yuqing; Yamaguchi, Doki; Lim, Seng; Witt, Peter; Piumsomboon, Pornpote; Chalermsinsuwan, Benjapon
Abstract: The chemical looping hydrogen production (CLHP) process is a new approach for hydrogen ( H 2 ) fuel production. The proposed process consists of three reactors which are air reactor (AR), fuel reactor (FR) and steam reactor (SR). In this study, the gas solid flow behaviour in a cold model of the proposed CLHP process was simulated using computational fluid dynamics (CFD) with kinetic theory of granular flow. The effect of drag coefficient models on the pressure profile of each reactor was investigated and the results from the modified Syamlal–O'Brien drag model agreed well with the experimental data. The model was further used to investigate effects of the operating parameters on the hydrodynamics profiles of each reactor. The solid flux increased with the increasing of inlet velocity of AR and FR but decreased with the increasing of the inlet velocity of SR. At the same time, the solid flux increased with the increasing of the solid inventory.